Proceedings of the Forty-Fifth Annual ACM Symposium on Theory of Computing 2013
DOI: 10.1145/2488608.2488693
|View full text |Cite
|
Sign up to set email alerts
|

Low-rank matrix completion using alternating minimization

Abstract: Alternating minimization represents a widely applicable and empirically successful approach for finding low-rank matrices that best fit the given data. For example, for the problem of low-rank matrix completion, this method is believed to be one of the most accurate and efficient, and formed a major component of the winning entry in the Netflix Challenge [17].In the alternating minimization approach, the low-rank target matrix is written in a bi-linear form, i.e. X = UV † ; the algorithm then alternates betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
881
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 772 publications
(895 citation statements)
references
References 18 publications
14
881
0
Order By: Relevance
“…Recently, there has been a resurgence of interest in methods based on alternating minimization, as numerous authors have shown that alternating minimization (suitably initialized, and under a few technical assumptions) provably converges to the global minimum for a range of problems including matrix completion [Kes12,JNS13,Har13], robust PCA [NNS + 14], and dictionary learning [AAJN13].…”
Section: Gordon's Generalizedmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, there has been a resurgence of interest in methods based on alternating minimization, as numerous authors have shown that alternating minimization (suitably initialized, and under a few technical assumptions) provably converges to the global minimum for a range of problems including matrix completion [Kes12,JNS13,Har13], robust PCA [NNS + 14], and dictionary learning [AAJN13].…”
Section: Gordon's Generalizedmentioning
confidence: 99%
“…, n}, the problem (10) has no known analytical solution, but it is still easy to fit a model using alternating minimization. Algorithms based on alternating minimization have been shown to converge quickly (even geometrically [JNS13]) to a global solution satisfying a recovery guarantee when the initial values of X and Y are chosen carefully [KMO09, KMO10, KM10, JNS13, Har13, GAGG13].…”
Section: Missing Data and Matrix Completionmentioning
confidence: 99%
See 2 more Smart Citations
“…See, for example, the reports in [19,33,43,44,59,77,116,186,287]. For recent analysis of this method, see [136].…”
Section: Alternating Least Squares (Als)mentioning
confidence: 99%